Assessment of AMR-ACB System Using Maghemite Nanoparticles in Theranostic Concentration - de Jesus Prates, Leopoldo (2020)
Alternating current biosusceptometry assembled with anisotropic magnetoresistive sensor (AMR-ACB) is a radiation-free technique that can enable the real-time monitoring of magnetic nanoparticles in biomedical applications. The aim of this study is to assess the capability of a multi-channel AMR-ACB system in detecting maghemite nanoparticles (MN) in concentrations used in therapeutic and diagnostic (theranostic) applications, such as oncology, multimodal anticancer therapy, or magnetic resonance imaging. The axial sensibility of the AMR-ACB system was successfully characterized in a bench-top study using MN in different concentrations and distances. The MN sample was aligned with the detection axis of the AMR-ACB system, and then it was moved at fixed distances from 0 to 16 mm. The test was repeated with different MN concentrations. The results show that the AMR-ACB system is capable of detecting samples of MN with a concentration of 0.3 mg/mL, and the output signal is directly proportional to the MN concentration. The output signal exhibits exponential decaying with distance, where the signal amplitude at 8.5 mm is approximately 10% of the signal at 0 mm. This work shows that the AMR-ACB system has adequate sensibility to be employed in in vivo studies to detect MN in theranostic concentrations as well as demonstrates the potential of this magnetic method as a possible tool for future diagnosis.